Small molecule modulation of p75NTR engages the autophagy-lysosomal pathway and reduces huntingtin aggregates in cellular and mouse models of Huntington's disease - Danielle A. Simmons; Namitha Alexander; Gloria Cao; Ido Rippin; Yarine Lugassy; Hagit Eldar-Finkelman; Frank M. Longo (Neurotherapeutics)
Huntington's disease (HD) is a neurodegenerative disorder caused by a CAG repeat expansion in the HTT gene encoding a mutant huntingtin (mHtt) protein. mHtt aggregates within neurons causing degeneration primarily in the striatum. There is currently a need for disease-modifying treatments for HD. Many therapeutic studies have focused on lowering mHtt levels by reducing its production or enhancing its clearance. One way to clear mHtt aggregates is to promote autophagy, which is disrupted in HD. Our previous studies showed that the small molecule p75 neurotrophin receptor (p75NTR) ligand, LM11A-31, prevented HD-related neuropathologies and behavioral deficits in multiple HD mouse models. This study investigated whether modulating p75NTR with LM11A-31, would reduce mHtt aggregates via autophagic/lysosomal mechanisms in HD models. LM11A-31 decreased mHtt aggregates in human neuroblastoma SH-SY5Y cells expressing mHtt (exon 1 with 74 CAG repeats) and in the striatum of R6/2 and zQ175dn mouse models of HD. The LM11A-31 associated decrease in mHtt aggregates in vitro was accompanied by increased autophagic/lysosomal activity as indicated by altered levels of relevant markers including p62/SQSTM1 and the lysosomal protease, mature cathepsin D, and increased autophagy flux. In R6/2 and/or zQ175dn striatum, LM11A-31 increased AMPK activation, normalized p62/SQSTM1 and LC3II levels, and enhanced LAMP1 and decreased LC3B association with mHtt. Thus, LM11A-31 reduces mHtt aggregates and may do so via engaging autophagy/lysosomal systems. LM11A-31 has successfully completed a Phase 2a clinical trial for mild-to-moderate Alzheimer's disease and our results here strengthen its potential as a candidate for HD clinical testing.